O minhoto Valentim : Senhor do Engenho São Romão - Crivelenti, Maria Amélia Assis Alves (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Drawing upon the case study of an immigrant from Minho (Northern Portugal), this article addresses several dimensions of the social structure in the region of Minas, in Mato Grosso (Brazil), in the 18th century.